ANALYSIS OF TRANSLATION TECHNIQUES IN TRANSLATING CULTURAL WORDS INTO INDONESIAN IN THE NOVEL “EAT, PRAY, LOVE” BY ELIZABETH GILBERT - Andriyanie, Reinata; Firmawan, Hendro; Retno, Tri Wahyu (Journal of Language and Literature, 2016)
The writer conducts this research to find what translation techniques which are applied by the translator in translating cultural words in the novel Eat, Pray, Love by Elizabeth Gilbert, and translated by Silamurti Nugroho. Here the writer uses the theory of Molina and Albir, because the writer thinks that the theory of Molina and Albir is the most appropriate theory for this research topic. The writer here uses qualitative and quantitative method in order to reach the goal of this research. The writer employs herself to collect data; Read the two versions of novel, they are Eat, Pray, Love by Elizabeth Gilbert and Makan, Doa, Cinta which is translated by Silamurti Nugroho, mark all the cultural words in the English version of the novel, find the equivalent in Indonesian version of the novel, classify the cultural words based on Newmark’s cultural words categories, select some of the data that are most appropriate with Newmark’s cultural words categories, and analyzed the selected data by using Molina and Albir’s theory of translation techniques. The result of this study shows that: eight translation techniques are applied by the translator in translating those cultural words.Keywords: Cultural Words, Translation Techniques Translation.